Sri Lanka S &T output during 2001- 2010: A scientometric asssessment - B.M, Gupta (Malaysian Journal of Library and Information Science, 2012)
This study analyses the research output of Sri Lanka in S&T during 2001-2010 on several parameters including its growth and global publications share, citation impact, share of international collaborative papers, contribution of major collaborative partner countries, contribution to various subject fields, geographical distribution of its papers, evaluation of the characteristics on its high productive institutions, authors and papers and the journals publishing the research output. The Scopus Citation Database has been used to retrieve the publication data for 10 years. The study concludes that Sri Lanka needs to increase its output and bring about improvement in the quality of its research efforts. This can be done by investing much more in research and development (R&D) expenditure, increase in the deployment of more qualified manpower and international collaboration; and by modernizing and strengthening its research infrastructure.